Novel self-oscillating class E ballast for compact fluorescent lamps. - Nerone, L.R (IEEE Transactions on power electronics)
A new, self-oscillating, class E ballast, well matched to low cost fluorescent lighting systems, is the focus of this paper. Precise analytical expressions are derived; valid for any duty ratio or circuit Q. This mathematical model is the basis for the design methodology. A qualitative analysis of the control system explains how the ballast operates from ignition to steady state. The transconductance of the switch provides the gain to initiate inverter oscillation. A simple technique of setting the duty ratio helps to match the avalanche voltage rating of the switch to the bus voltage. Current limiting prevents damage to the switch, during the initial turn-on. Experimental results validate the model